2014
DOI: 10.1007/s10461-014-0896-7
|View full text |Cite
|
Sign up to set email alerts
|

Daily Associations Between Alcohol Use and Unprotected Anal Sex Among Heavy Drinking HIV-Positive Men Who Have Sex with Men

Abstract: Men who have sex with men (MSM) account for the largest proportion of new HIV infections in the United States. Alcohol may facilitate HIV transmission by increasing unprotected anal sex, but few studies have focused on transmission behaviors in HIV-positive MSM. This study explored daily associations between alcohol use and sexual behavior among heavy drinking HIV-positive MSM using a 30-day Timeline Followback interview. Results of generalized estimating equations indicated that greater alcohol consumption on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
48
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 40 publications
11
48
1
1
Order By: Relevance
“…Compared to Light users variables associated with Alcohol/marijuana class were lack of health insurance, younger age and greater odds of anal sex under the influence. The finding that both Alcohol/marijuana and Poly-user classes were significantly more likely to engage in sex under the influence is consistent with literature on the association between heavy and binge alcohol use and unprotected sex (27,28). The reduced rate of health insurance among this group may provide insight into the low rates of substance abuse treatment access and utilization, previously observed in this population.…”
Section: Discussionsupporting
confidence: 89%
“…Compared to Light users variables associated with Alcohol/marijuana class were lack of health insurance, younger age and greater odds of anal sex under the influence. The finding that both Alcohol/marijuana and Poly-user classes were significantly more likely to engage in sex under the influence is consistent with literature on the association between heavy and binge alcohol use and unprotected sex (27,28). The reduced rate of health insurance among this group may provide insight into the low rates of substance abuse treatment access and utilization, previously observed in this population.…”
Section: Discussionsupporting
confidence: 89%
“…Overall, these findings are consistent with other data regarding the role of event-level substance use (Chiasson et al, 2007; Colfax et al, 2004; Drumright et al, 2006a; Lambert et al, 2011), including a recent study of HIV-positive GBMSM that found daily alcohol and drug use were both associated with an increased odds of anal intercourse and CAS while adjusting for individual frequency of use (Kahler et al, 2015). However, unlike the research by Kahler et al and other studies, ours is one of the first to identify a reciprocal association between higher frequency use and both sexual engagement and CAS while accounting for event-level use, which was particularly true for marijuana, though also partially true for club drugs and heavy drinking for sexual engagement as well as at least one of the models of CAS for each.…”
Section: Discussionsupporting
confidence: 89%
“…Briefly, male heavy drinkers living with HIV were recruited from an urban health center with extensive experience providing HIV clinical care (for details see Kahler et al, 2014). Participants were randomized either to treatment-as-usual or to a brief motivational intervention to reduce alcohol use plus treatment-as-usual.…”
Section: Methodsmentioning
confidence: 99%